PENGEMBANGAN MEDIA PEMBELAJARAN IPA BERBANTUAN NEARPOD UNTUK MENINGKATKAN KEMANDIRIAN DAN HASIL BELAJAR SISWA - Suci Apriana; Tity Kusrina; Rahmad Agung N (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The use of appropriate and engaging learning media will certainly motivate students in the learning process, both in the classroom and at home. To create an interesting, interactive, and enjoyable science learning experience, teachers, as learning facilitators, need to seek solutions. This way, students are not solely reliant on classroom learning with textbooks and worksheets as their only learning resources. This research aims to enhance students' independence and learning outcomes through the development of interactive science learning media assisted by the Nearpod application. Nearpod offers features that align with the demands of learning, from material presentation to interactive learning evaluations, thereby expected to foster students' independent learning. The research method used is Research and Development (R&D), a type of research and development method where the product development model or procedure follows the ADDIE model. The ADDIE model is one of the instructional design system models that outlines basic stages of a simple and easy-to-learn learning system design, depicting a systematic approach. As the name suggests, the ADDIE model consists of five main phases: (A)nalysis, (D)esign, (D)evelopment, (I)mplementation, and (E)valuation. The findings of this study indicate that the development of Nearpod-assisted science learning media is effective in improving students' independence and learning outcomes. It is also deemed effective in enhancing students' understanding of the material